2022
DOI: 10.26508/lsa.202201476
|View full text |Cite
|
Sign up to set email alerts
|

OXSR1 inhibits inflammasome activation by limiting potassium efflux during mycobacterial infection

Abstract: Pathogenic mycobacteria inhibit inflammasome activation to establish infection. Although it is known that potassium efflux is a trigger for inflammasome activation, the interaction between mycobacterial infection, potassium efflux, and inflammasome activation has not been investigated. Here, we use Mycobacterium marinum infection of zebrafish embryos and Mycobacterium tuberculosis infection of THP-1 cells to demonstrate that pathogenic mycobacteria up-regulate the host WNK signalling pathway kinases SPAK and O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…It is involved in the stress response pathway, actively regulating the p38 MAP kinase pathway and TCR signaling in naive CD4+ T cells. It is well-known for its role in inflammatory diseases, macrophage activation, and bacterial growth [ 97 , 98 ]. According to research, STK39 dysregulation affects MMP2 (matrix metallopeptidase 2) and MMP9 (matrix metallopeptidase 9), thus actively participating in osteosarcoma [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in the stress response pathway, actively regulating the p38 MAP kinase pathway and TCR signaling in naive CD4+ T cells. It is well-known for its role in inflammatory diseases, macrophage activation, and bacterial growth [ 97 , 98 ]. According to research, STK39 dysregulation affects MMP2 (matrix metallopeptidase 2) and MMP9 (matrix metallopeptidase 9), thus actively participating in osteosarcoma [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Hortel et al ( 2022 ) employed zebrafish embryos infected with M. marinum and in vitro THP-1 macrophage– M. tuberculosis systems to investigate the role of the WNK-OSXR1 signaling pathway in infection-induced inflammasome activation. The research demonstrated that pathogenic mycobacteria, particularly M. marinum , elevate macrophage K+ concentration and induce the expression of OXSR1.…”
Section: Exploration Of Host-directed Approaches In Zebrafish Embryo ...mentioning
confidence: 99%
“…The aim of testing cancers is very often to discover the function of genes. In this case, the commonly used method is (again) CRISPR, which enables editing of the genome and alters gene transcription [ 98 ]. For investigation of gene function, the most common methods are based on immunochemistry [ 99 ] or genes expression analysis by qPCR [ 98 ].…”
Section: Aim Of the Studies—what Is The Point?mentioning
confidence: 99%
“…In this case, the commonly used method is (again) CRISPR, which enables editing of the genome and alters gene transcription [ 98 ]. For investigation of gene function, the most common methods are based on immunochemistry [ 99 ] or genes expression analysis by qPCR [ 98 ]. In cancer cells, such as any other, every event is promoted by a number of genes involved in many different signaling pathways.…”
Section: Aim Of the Studies—what Is The Point?mentioning
confidence: 99%
See 1 more Smart Citation